PENGARUH INFLASI, NILAI TUKAR, DAN BELANJA PEMERINTAH DAERAH TERHADAP PENANAMAN MODAL DALAM NEGERI DI PROVINSI JAWA TENGAH - Didi Zainuddin; Anita Ria; Pudji Astuty (JABE (Journal of Applied Business and Economic), 2021)
This study discusses the relationship between inflation, exchange rates, and local government spending on domestic investment (PMDN) in Central Java Province while this study uses SPSS in processing data, and the results of this study stated that from the test results the regression model is obtained for the equation The multiple linear regression of this research is Y = -46.571 – 0.347 Inflation + 1.509 Exchange Rate + 1.402 Regional Expenditures + e. With constant (a) = -46.571 Regression coefficient X_1 (b_1) = -0.347 Regression coefficient X_2 (b_2) = 1.509, while the regression coefficient X_3 (b_3) = 1.402. For the results of the Simultaneous Significance Test. (F – statistical test). F_count is used to test whether the equation model Y = a + b_1 X_1 + b_2 X_2 + b_3 X_3 or the regression equation Y = -46.571 – 0.347 X_1 + 1.509 X_2 + 1.402 X_3. F_hitung = 10.355 and F_tabel 0.05 = 4.76. Because F_hitung > F_table that is (10.355 > 4.76) based on this research method, it can be stated the truth of the model used. And t is stated that the probability obtained is 0.009 < 0.05. So the conclusion of the independent variable (Inflation, Exchange Rates and Regional Expenditures) together have a significant impact on the dependent variable (domestic investment).